2013
DOI: 10.1371/journal.pone.0082639
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV Inhibition Activates CREB and Improves Islet Vascularization through VEGF-A/VEGFR-2 Signaling Pathway

Abstract: Substitution of pancreatic islets is a potential therapy to treat diabetes and it depends on reconstitution of islet’s capillary network. In this study, we addressed the question whether stabilization of Glucagon-Like-Peptide-1 (GLP-1) by inhibiting Dipeptidyl Peptidase-IV (DPP-IV) increases β-cell mass by modulating vascularization. Mouse or porcine donor islets were implanted under kidney capsule of diabetic mice treated with DPP-IV inhibitor sitagliptin. Grafts were analyzed for insulin production, β-cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…In addition to reducing blood glucose concentration, sitagliptin has displayed diverse pharmacological effects. For example, a recent study demonstrated that treatment with sitagliptin increases β‐cell mass and islet vascularization through activating the transcriptional factor cAMP‐response element binding (CREB) protein . Notably, CREB has been reported to play a central role in regulating the expression of PGC‐1α .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to reducing blood glucose concentration, sitagliptin has displayed diverse pharmacological effects. For example, a recent study demonstrated that treatment with sitagliptin increases β‐cell mass and islet vascularization through activating the transcriptional factor cAMP‐response element binding (CREB) protein . Notably, CREB has been reported to play a central role in regulating the expression of PGC‐1α .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, DPP IV/CD26 inhibition improved functional blood flow in grafts as a result of inhibitor acting. It is shown that sitagliptin improves VEGF secretion in transplanted porcine islets, which contributes to cell proliferation and angiogenesis by increasing VEGFR-2 expression [28]. DPP IV/CD26 inhibition with linagliptin also showed decreased blood glucose levels and accelerated skin re-epithelization in diabetic mice since levels of active GLP-1 in wound lysates increased.…”
Section: Dpp Iv/cd26 Inhibitors In Treatment Of Diabetesmentioning
confidence: 99%
“…However, its biological availability is controlled by dipeptidyl peptidase IV (DPP IV/CD26), a moonlighting protein with an enzymatic function which cleaves active GLP-1. One of the most important implications of DPP IV/CD26 inhibitors is indeed therapeutic support of DM, where it found its clinical importance, given its capability to contribute to the maintenance of glucose homeostasis [8].…”
Section: Therapeutic Approaches In Diabetesmentioning
confidence: 99%
“…Other opinions demonstrate that it can activate signal transducer and activator of transcription 3 (STAT3) signaling, developing pancreatic microvasculature [75]. Sitagliptin, a Dipeptidyl Peptidase IV Inhibition, can activate cAMP response element-binding (CREB) in β cell, increase VEGF secretion, inducing neovascularization of islets [76].…”
Section: Connective Tissue Growth Factormentioning
confidence: 99%